Differences in experiences of barriers to STI testing between clients of the internet-based diagnostic testing service GetCheckedOnline.com and an STI clinic in Vancouver, Canada. (7th February 2018) - Gilbert, Mark; Thomson, Kimberly; Salway, Travis; Haag, Devon; Grennan, Troy; Fairley, Christopher K; Buchner, Chris; Krajden, Mel; Kendall, Perry; Shoveller, Jean; Ogilvie, Gina
Abstract : Objectives: Internet-based STI testing programmes may overcome barriers posed by in-clinic testing, though uptake could reflect social gradients. The role these services play in comparison to clinical testing services is unknown. We compared experiences of testing barriers between STI clinic clients to clients of GetCheckedOnline.com (GCO; where clients take a printed lab form to a lab). Methods: Our 10-month cross-sectional study was conducted after GCO was promoted to STI clinic clients and men who have sex with men (MSM). Clinic and GCO clients completed an online survey assessing testing barriers and facilitators; responses were compared using bivariate analysis (level of significance P<0.01; significant results below). Results: Compared with 321 clinic clients, the 73 GCO clients were more likely to be older (median 35 vs 30 years), MSM (45% vs 16%), be testing routinely (67% vs 39%), have delayed testing for any reason (76% vs 54%) and due to clinic distance (28% vs 9%), report delays due to wait times (50% vs 17%), embarrassment with testing (16% vs 6%), discomfort discussing sexual health where they usually go for testing (39% vs 22%), as well as discomfort discussing sexual history with (19% vs 5%) and fearing judgement from (30% vs 15%) any healthcare provider. GCO clients were less likely to have found clinic hours convenient (59% vs 77%) and clinic appointments easy to make (49% vs 66%), and more likely to report long wait times (50% vs 17%). We found no differences in technology skills/use. Conclusions: In this urban setting, an internet-based testing service effectively engaged individuals experiencing testing barriers, with few social gradients in uptake. While some testing barriers could be addressed through increasing access to clinical services, others require social and structural changes, highlighting the importance of internet-based STI testing services to increasing test uptake.